2021
DOI: 10.1108/ijchm-11-2020-1324
|View full text |Cite
|
Sign up to set email alerts
|

Country-of-origin cues: effects of country-related affect and product association on consumer responses to hospitality firms

Abstract: Purpose This paper aims to investigate the impacts of country-of-origin (COO) cues, country-related affect (CRA) and country-related product associations (CRPA) on consumers’ intention to purchase hotel services. Design/methodology/approach A survey of 305 respondents was conducted. Mediation and conditional process tests were performed to examine the proposed theoretical framework. Findings The results suggest that CRA is positively correlated with consumer trust, which, in turn, affects purchase intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
0
2
0
2
Order By: Relevance
“…As snowball sampling method can help researchers approach more research population (Sobaih et al , 2021) and it is widely used in recent hospitality studies to collect data (Li and Xie, 2021; Singh et al , 2021), we chose to use snowball sampling for data collection. Through our relationship with 9 hospitality organizations, we connected with 23 restaurants and 5 hotels.…”
Section: Methodsmentioning
confidence: 99%
“…As snowball sampling method can help researchers approach more research population (Sobaih et al , 2021) and it is widely used in recent hospitality studies to collect data (Li and Xie, 2021; Singh et al , 2021), we chose to use snowball sampling for data collection. Through our relationship with 9 hospitality organizations, we connected with 23 restaurants and 5 hotels.…”
Section: Methodsmentioning
confidence: 99%
“…Consumer ethnocentrism is strongly associated with the importance of country-of-origin information on the food label [13]. The influence of country-related effect on trust is negatively related to consumer ethnocentrism [14].…”
Section: Introductionmentioning
confidence: 99%
“…tia: people traveling abroad and having a more expressed interest in traveling abroad have a higher level of CE than those who travel less and have a lower desire to travel abroad. Another unusual finding was that younger people have more pronounced tendencies of CE than older people Li and Xie (2021). found that in the hospitality industry, the effect of country-related affect on trust (which affects purchase intention) is weaker for consumers with a high level of consumer ethnocentrism Cassia and Magno (2022).…”
mentioning
confidence: 98%